Latent toxoplasmosis and olfactory functions of Rh positive and Rh negative subjects - Flegr, Jaroslav; Milinski, Manfred; Kaňková, Šárka; Hůla, Martin; Hlaváčová, Jana; Sýkorová, Kateřina (PloS one, 2018)
The prevalence of toxoplasmosis is higher in schizophrenics than in the general population. It has been suggested that certain symptoms of schizophrenia, including changes in olfactory functions, are in fact symptoms of toxoplasmosis that can be easily detected in schizophrenics only due to the increased prevalence of toxoplasmosis in this population. Schizophrenics have impaired identification of odors and lower sensitivity of odor detection, however, no information about these parameters of non-schizophrenic Toxoplasma-infected subjects is available. Here we searched for differences in olfactory functions between 62 infected and 61 noninfected non-schizophrenic subjects using the case-controls experimental design. The infected men scored better than the non-infected controls in the standard odor-identification test. The infected women rated all smells as more intensive while the infected men rated nearly all smells as less intensive. Infected women rated the pleasantness of the smell of the cat urine as higher than the non-infected women and the opposite was true for the men-in contrast, higher pleasantness of odor in infected men and lower in infected women were observed and described in the 2011 study. Toxoplasmosis, Rh, and toxoplasmosis-Rh interaction were not associated with the rated pleasantness of the smell of other stimuli. However, our sample contained only 17 Rh negative men and 30 Rh negative women. Therefore, all results concerning the main effects of Rh factor and the interaction with Rh factor must be considered only preliminary. Our results suggest that latent toxoplasmosis is associated with changes in the olfactory functions in humans; however, the observed changes differ from those observed in schizophrenics.